Delay discounting of rewards and losses, alcohol use, and the influence of socioeconomic factors: a cross-sectional online study in frequent drinkers - Pinger, Mathieu; Skirke, Malin; Thome, Janine; Sommer, Wolfgang H.; Koppe, Georgia; Kirsch, Peter (Alcohol, 2024)
Background Delay discounting describes the devaluation of future outcomes over time and is a popular behavioral construct in addiction research. Prior studies show modest yet consistent associations between problematic alcohol use and delayed reward discounting (DRD). However, the potential confounding influence of socioeconomic status (SES, e.g., income and education) is rarely addressed. In this study, we aimed to investigate the robustness of DRD as a predictor of alcohol use after controlling for socioeconomic and demographic variables. Additionally, we aimed to test the association between delayed loss discounting (DLD) and alcohol use in a sufficiently large sample. Methods We collected data from 341 moderate-to-heavy-drinking participants (27.92 ± 21.12 g alcohol/day, 43.48 ± 11.90 years old, 49.9% female, UK residents) in a cross-sectional online study. DRD and DLD were measured using an intertemporal choice task. Questionnaires encompassed alcohol use (AUDIT, weekly alcohol consumption), education and income, subjective measures of past and present socioeconomic status, and impulsivity. Results DRD, but not DLD, was significantly associated with AUDIT scores (r = 0.15) and weekly alcohol consumption (r = 0.12). DRD remained a significant yet weak predictor of AUDIT scores when controlling for education and income, but not when controlling for education and age. Conclusions We replicated a small but robust association between alcohol use and DRD, but not DLD. This association appeared to be confounded by education and age, but not by income. We conclude that socioeconomic and demographic variables should systematically be accounted for in future studies investigating DRD and alcohol use.
Gesehen am 01.04.2025